LEXICAL AND CONTEXTUAL MEANING IN ALAN WALKER SONG LYRIC AT WORLD OF WALKER ALBUM - Sri, Sri Hartati Baene (Research on English Language Education, 2023)
Song lyric is one of literary works and it is has meaning. Song lyric contain word and language that expose the author’s thought and feeling. So may people in this world like to listen to the song. But sometimes the listener confused to understand what the song writer mean or what the meaning of the song because sometimes in the song lyric has the same words but has different meaning. This research was aimed to analyze lexical and contextual meaning expression found in Alan Walker song lyric at World of Walker album. This research designed by using qualitative descriptive method. In analyzing the data, the researcher used theory of Creswell. The source of the data in this study was taken from the Alan Walker song lyric at World of Walker album that was obtained from internet by downloaded the lyric from of the song. The data of this research are word, phrase and sentence in the lyrics that exist the album. Based on the result of research, it was found that there were 34 expressions that contain contextual meaning. There are expressions in the form of word and phrases, generally those expression are related to a person’s feelings or expression. On the other side, the lexical meaning form are only expressions that contain contextual meaning.